Food safety interventions in the bakery industry : microbial safety from wheat milling to finished baked products - Vega, Daniel (Kansas State University, 2021)
Validation studies are a critical tool to control pathogens in food products for human consumption. Data from these studies lay the scientific foundation for strong food safety programs in processing plants to better ensure public health. Even though flour has been considered for years as microbiologically safe, there have been recent foodborne outbreaks associated with flour. Therefore, the first objective of this work was to validate the safety of flour during wheat tempering by the use of water or lactic acid (LA) at five different tempering temperatures (ambient, 120°, 130°, 140°, and 150°F) at two inoculation levels. Ambient water treatment resulted in a 0.4 log CFU/g reduction over 24 h of tempering at both inoculation levels, whereas ambient LA tempering reduced the Salmonella population by 1.2 and 1.4 log cycles at T0 (immediately after application) for low and high inoculation levels, respectively. By 12 h of ambient tempering of low-level inoculated wheat, only 1 of 3 replications indicated residual Salmonella viability, while two were negative by enrichment. For the high-inoculation level wheat, a 2.4 log CFU/g reduction was observed after 12 h and no further reductions were noted up to 24 h of tempering. For high inoculation level wheat, increasing tempering temperature for LA application to 130°F resulted in >5 log CFU/g reductions by 4 h, and no Salmonella was detected by enrichment at 140 and 150°F at any tempering time. The second to fourth objectives of this research were to validate a representative commercial oven baking process for the manufacture of cheesecake, fruit-filled pastries, and peanut butter bars against mixed inocula of pathogens. For cheesecake, it was found that the mean internal temperature increased from 17°C to ~97°C at the end of 50 min baking. The Salmonella population in cheesecake decreased by >5 log CFU/g by 37.5 min of baking and was completely eliminated after 50 min of baking (as determined by enrichment). The pH and water activity of cheesecake after baking and cooling were 4.86 and 0.943, respectively. D-values of the Salmonella cocktail at 55, 58 and 61°C were 27.4, 13.8 and 4.9 min, respectively, whereas the z-value of the Salmonella cocktail was 8.2°C. For fruit-filled pastries, the mean internal temperature increased from 36.7°C to ~101°C at the end of 15 min baking. The Salmonella population in pastries decreased by >5 log CFU/g by 9 min of baking and was completely eliminated after baking and cooling (as determined by enrichment). The pH and water activity of pastries after baking and cooling were 5.33 and 0.677, respectively. D-values of the Salmonella cocktail at 55, 58 and 61°C were 32.8, 15.5 and 5.3 min, respectively, with a z-value of 7.7°C for the Salmonella cocktail determined. For peanut butter bars, internal temperature of the bars increased from ~25°C to ~91°C during 13 min of baking. Salmonella, Shiga toxin-producing E. coli, and L. monocytogenes population reductions (P ≤0.05) were 2.4, 3.0, and 3.9 logs CFU/g, respectively, compared to raw dough levels. Water activity of bars decreased from 0.81 to 0.70, while pH increased from 7.0 to 8.7 during baking. Respective D-values (min) for Salmonella and STEC in aw[subscript]-adjusted dough were 9.4 and 10.2 at 85°C; 3.9 and 3.3 at 90°C; and 1.7 and 1.7, at 92.5°C, respectively. The calculated z-values for Salmonella and STEC were 10.1 and 10.1 respectively. The fifth study of this work involves the comparison of a hamburger inoculation study versus a surface inoculation study. During this research we obtained a 5.7 log CFU/g reductions of the hamburger surface inoculated bun versus a full lethality in a previous study, demonstrating differences between crust and crumb. The aw[subscript] of the crust decreased significantly (p≤0.05) during baking, while the crumb aw[subscript] had a similar value at the end of baking. This study demonstrates the importance of evaluating lethality differences between surface and internal parts of a bakery product.
Keywords: Food microbiology; Food safety; Bakery; Wheat milling